Coagulopathy in Isolated Traumatic Brain Injury: Myth or Reality - Mathur, Rohan; Suarez, Jose I. (Neurocritical care, 2023)
Introduction Traumatic Brain Injury (TBI) has been shown to be associated with altered hemostasis and coagulopathy, that correlates with worsening secondary injury and clinical outcomes. Isolated Traumatic Brain Injury (iTBI), that is TBI without significant extracranial injuries, has also been shown to be associated with systemic coagulopathy and derangements in hemostasis. Methods Literature Review. Results Present your results in logical sequence in the text, tables, and figures, giving the main or most important findings first. Do not repeat all the data in the tables or figures in the text; emphasize or summarize only the most important observations. Provide data on all primary and secondary outcomes identified in the Methods section. Give numeric results not only as derivatives (e.g. percentages) but also as the absolute numbers from which the derivatives were calculated, and specify the statistical significance attached to them, if any. Discussion In this review, we provide an overview of the pathophysiology of the hemostatic disturbances caused by iTBI, review key clinical findings and discrepancies in the way this question has been approached, describe the use and role of global viscoelastic assays such as the thromboelastrogram, and detail principles for reversal of pre-injury blood thinners. Conclusions iTBI is clearly associated with the development of coagulopathy, but the extent to which it occurs is confounded by the fact that many of the studies have included patients with moderate extracranial trauma into the iTBI category. The coagulopathy itself has been better studied in preclinical models, and the mechanisms driving it suggest a pattern consistent with disseminated intravascular coagulation with hyperfibrinolysis. We provide pragmatic clinical takeaways and suggestions for future research.